Genetic mapping of leaf rust (Puccinia triticina Eriks) resistance genes in six Canadian spring wheat cultivars - Bokore, Firdissa E.; Cuthbert, Richard D.; Knox, Ron E.; Hiebert, Colin W.; Pozniak, Curtis J.; Berraies, Samia; Ruan, Yuefeng; Meyer, Brad; Hucl, Pierre; McCallum, Brent D. (Frontiers in Plant Science, 2023)
The Canada Western Red Spring wheat (Triticum aestivum L.) cultivars AAC Concord, AAC Prevail, CDC Hughes, Lillian and Glenlea, and elite line BW961 express a spectrum of resistance to leaf rust caused by Puccinia triticina Eriks. This study thought to identify and map the leaf rust resistance of the cultivars using three doubled haploid populations, AAC Prevail/BW961 (PB), CDC Hughes/AAC Concord (CHC) and Lillian/Glenlea (LG). The populations were evaluated for seedling resistance in greenhouse and adult plant disease response in the field at Morden, MB for three years and genotyped with the 90K wheat Infinium iSelect SNP array. Genetic maps were constructed to perform QTL analysis on the seedling and field leaf rust data. A total of three field leaf rust resistance QTL segregated in the PB population, five in the CHC and six QTL segregated in the LG population. In the PB population, BW961 contributed two QTL on chromosomes 2DS and 7DS, and AAC Prevail contributed a QTL on 4AL consistent across trials. Of the five QTL in CHC, AAC Concord contributed two QTL on 4AL and 7AL consistent across trials, and a QTL on 3DL.1 that provided seedling resistance only. CDC Hughes contributed two QTL on 1DS and 3DL.2. Lillian contributed four QTL significant in at least two of the three trials on 2BS, 4AL, 5AL and 7AL, and Glenlea two QTL, on 4BL and 7BL. The 1DS QTL from CDC Hughes, the 2DS from BW961, the 4AL from the AAC Prevail, AAC Concord and Lillian, and the 7AL from AAC Concord and Lillian conferred seedling leaf rust resistance. The QTL on 4AL corresponded with Lr30 and was coincident the same across cultivars AAC Prevail, AAC Concord and Lillian, whereas the 7AL corresponding with LrCen was coincident between AAC Concord and Lillian. The 7DS and 2DS QTL in BW961 corresponded with Lr34 and Lr2a, respectively, the 1DS QTL in CDC Hughes with Lr21. The QTL identified on 5AL could represent a novel gene. The results of this study will widen our knowledge of leaf rust resistance genes in Canadian wheat and their utilization in resistance breeding.